Diversity and pest control potential of Hymenopteran parasitoids of Ceratitis spp (Diptera, Tephritidae) from mangos in Mali - Vayssières, Jean-François; Wharton, R.; Delvare, G.; Sanogo, F. (2004)
In Mali, 1205 mangos (Mangifera indicaL.) were sampled between April and September 2000 andplaced under observation. We recovered 7518 adults of six species of Ceratitis, namely C. cosyra (Walker), C. silvestriiBezzi, C. quinaria (Bezzi), C. fasciventris (Bezzi), C. anonae Graham and C. ditissima (Munro). A total of 436 hymenopteran parasitoids belonging to eight species were recovered from the fruit flies: Psyttalia perproximus(Silvestri), P. cosyrae (Wilkinson), Fopius caudatus (Szépligeti), Diachasmimorpha fullawayi (Silvestri) (all Braconidae, Opiinae); Asobara sp. (Braconidae, Alysiinae); Tetrastichus giffardianus Silvestri (Eulophidae, Tetrastichinae); Spalangia simplex Perkins, Pachycrepoideus vindemiae (Rondani) (Pteromalidae, Pteromalinae). The most abundant parasitoid species were P. cosyrae, F. caudatus and P. vindemiae. The opiines (koinobionts) are the most abundant group of tephritid parasitoids and are more frequently used in integrated pest management programmes. Other families of parasitoids, such as Eulophidae (koinobionts) and Pteromalidae (idiobionts), are infrequently used for tephritid biological control as very little is known about the role of these micro-hymenopterans in controlling tephritid larvae. Data on their life cycle and host specificity will therefore be valuable in determining their role in complementing the impact of the opiines on the biological control of tephritid larvae. This paper presents the first results of such a study.